Climate Change and the Inuvialuit of Banks Island, NWT: Using Traditional Environmental Knowledge to Complement Western Science - Riedlinger, Dyanna (ARCTIC, 1999)
. Western science, while a valuable means of acquiring knowledge, represents only one set of approaches to knowledge and inquiry. An exclusive focus on scientific data may limit our understanding of climate change and its impact on western Arctic communities. Can other approaches to knowledge and inquiry enhance our understanding? One way to broaden this understanding is to explore the contribution of traditional environmental knowledge. As an example of how to bridge the gap between scientific and traditional knowledge, I will describe how Inuvialuit environmental knowledge, or local expert knowledge of the land, can enhance research on climate change. Recorded here are my first impressions of a project to document climate change as it is seen through the eyes of the Inuvialuit of Banks Island. .